Find the product.

(x-4)² + (x-2)² + (x-3)²

Find the product.

(x-4)² + (x-2)² + (x-3)²

Tutors, please sign in to answer this question.

(x-4)² + (x-2)² + (x-3)²

= x^{2} -8x+16 + x^{2} -4x +4 + x^{2}-6x +9

= 3x^{2}-18x +29

= (x-4)(x-4) + (x-2)(x-2) + (x-3)(x-3)

= x^{2}-4x -4x +16 + x^{2} -2x -2x +4 + x^{2}-3x - 3x + 9

= x^{2} + x^{2} + x^{2}-8x -4x -6x +16 +4 +9

= 3x^{2} - 18x +29

Alex C.

Harvard/MIT Finance and Statistics Tutor

Fort Lee, NJ

5.0
(263 ratings)

Steven L.

Cornell Alum - Enthusiast in Math and Science (Regents, SAT/ACT, AP)

Fresh Meadows, NY

4.9
(146 ratings)

Romina A.

Knowledgeable tutor in Spanish, Biology, Anatomy & Physiology and Math

Harrison, NJ

5.0
(175 ratings)